Calibration Altimeter Sites at Cape of Begur and Ibiza Island - Martínez Benjamín, Juan José; Martínez García, Marina; Ortiz Castellón, Miquel Ángel; Rodríguez Velasco, Gema; Garate Pasquin, Jorge; Bonnefond, Pascal; Pérez Gómez, Begoña; García Silva, Cristina; Martín Dávila, José (Física de la Tierra, 2005)
The three Begur experiments have been conducted on March, 16-19, 1999, which was the first altimeter calibration ever developed in Spain and the first Alt-B altimeter calibration made in the Mediterranean Sea; on July, 4-7, 2000, and on August, 25-28, 2002. Direct absolute altimeter calibration, estimating the TOPEX Alt-B bias, was made from direct overflights using GPS buoys. This method does not require any modelling of geoid and tidal error. Other main objective of the campaigns was to map with GPS buoys the Mean Sea Surface, MSS, along an ascending T/P groundtrack about 15-20 km from the coast, using coastal tide gauge measurements. This method requires geographical mapping of geoid and ocean tides which reduces the accuracy of the bias estimate by a factor of two. Indirect absolute altimeter calibration is possible for any satellite crossing the MSS, with the only requirement that tide gauges are operational during the overflight. In the framework of the JASON-1 CNES/NASA mission, a campaign was conducted on June 9-17, 2003, in the Absolute Calibration Site of the Island of Ibiza. The objective was to determine the local marine geoid slope under the ascending (187) and descending (248) Jason-1 ground tracks, in order to allow a better extrapolation of the open-ocean altimetric data with on-shore tide gauge locations, and thereby improve the overall precision of the calibration process. We present preliminary results on Jason-1 altimeter calibration using the derived marine geoid: from this analysis the altimeter bias is estimated to be 120 ±5 mm.